Enhanced Pv Solar Power System Design with An Mppt Controller as A Function of Temperature - et. al., I.Rahula, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In order to achieve optimum point tracking (MPPT) for the selection of the highest power consumption, the photovoltaic (PV) system was improved. The output power of the PV effect depends on external solar irradiation and the ambient temperature. In the existing MPPT approaches, most take only radiation fluctuations into account, with limited consideration of the consequences of temperature shifts. But the temperature coefficients (TCs), especially in applications where changes in ambient temperature are relative high, play an important role in the PV system. A correct study for the MPPT method was performed with a PV system which considers the temperature change using a variable universe fuzzy logic control (VUFLC). Taking account of the changing atmosphere temperature in photovoltaic panels, the proposed control method will regulate VUFLC contraction and expansion, removing the effect of temperature fluctuations and improving MPPT efficiency and thus achieving a quick and accurate tracking control. The proposed strategy was tested under different environmental conditions for a PV module and its control efficiency is compared with simulation and experimental results to other MPPT strategies. Compared with fossil fuels, the best alternative is to generate photovoltaic energy every day. In future, because of the above developments the thermal and nuclear power plant will probably withdraw. The cost of development and installation are rising in comparison with other renewable options. The article addresses a better configuration with an MPPT controller for a PV solar power system compared to other strategies dealing with the non-shaded, partial shading of variable sun-irradiance. This helps designers and maintainers build maintenance processes and phases.